Advanced composite adsorbent based on biochar, bentonite, and boric acid for sustainable removal of Pinoxaden - Shakir, Safa Waleed; Al-Yaqoobi, Atheer Mohammad (International Journal of Renewable Energy Development, 2025)
Pinoxaden is a post-emergence herbicide, which is widely applied for the control of wheat, barley, and other cereals. Its usage is increasing across the world, and there have been concerns regarding contamination of water bodies due to residues. In this research, we investigated the removal of Pinoxaden by a new boric-acid-activated biochar–bentonite composite. The composite was synthesized by pyrolyzing biomass with boric acid and bentonite clay. The composite was studied using XRD, SEM, FTIR, and BET analysis, which showed that it has a very porous structure and boron–oxygen features on its surface. Batch adsorption experiments (pH variation, time variation, and variation of initial concentration) demonstrated rapid uptake with high capacity. Kinetic analysis was pseudo-second-order, and equilibrium data obeyed the Langmuir isotherm, indicative of monolayer chemisorption. Researchers realized maximum adsorptive capacities of 150 mg/g, within the range of 5–100 mg/g. The removal efficiency was found, through a batch adsorption study, to be a maximum of more than 99.5% at optimum conditions. Increased Pinoxaden concentration and topped-up adsorbent loading reduced the adsorptive capacity but increased with maximum adsorbent loading. The data followed the Freundlich isotherm (R² > 0.999), which shows that the adsorption happens in multiple layers, and it matched the pseudo-second-order model, indicating that the process involves chemical bonding. Studies on how substances move within particles and how they come off showed that the surface features and the movement through pores were more important than the overall amount taken in. We found that adding boric acid significantly increased the polarity and reactivity by boosting the adsorptive capacity from raw biochar or bentonite. The research shows that the MC-Db composite could be a useful, eco-friendly material that effectively removes herbicides from contaminated water.